Street-connected Children Counselling and Guiding Them: A Critical Literature Review - Julien, Gabriel (Cipta Pustaka Nusantara, 2025)
Globally, the issue of street-connected children continues to be a growing phenomenon. This scenario is very convoluted to comprehend since there are various factors that contribute to their presence on the streets. To try to understand their lives and bring hope to them via counselling, this critical review systematically searched various journals and articles for references pertaining to the topic. This non-empirical research is advantageous because it can provide theoretical insights, develop new concepts, and synthesize existing knowledge through literature reviews. Mention must be made of its limitations. It lacks empirical evidence which makes the findings potentially subjective, leading to conclusions that can be less reliable and harder to verify through experimentation or direct observation. Nonetheless, the findings identified that street-connected are habitually viewed as victims of poverty, abuse, violence, and discrimination. The findings also revealed that although their lives are constantly rooted in danger it is not impossible to rehabilitate and provide them with counselling and guidance. Moreover, these children have the innate capacity to navigate complex situations, adapt to street life, and build supportive networks. These diverse perspectives shape how society perceives and responds to street-connected children and influence the types of support and interventions provided. Thus, this analysis raises an awareness about their plight and calls supporting organizations to continue to advocate for their rights. While these various organizations provide street-connected children with basic amenities like food, clothing, and shelter, they should also concentrate on long-term solutions such as counselling and guidance and integration.